Evaluation of green manures in different sowing dates and row-spacings in the cerrados region - Amabile, Renato Fernando (2000)
In 1991/1992 growing season, three field experiments were carried out to evaluate the growth and development of sunn (Crotalaria juncea), Crotalaria ochroleuca, black velvet bean (Mucuna aterrima), pigeon pea cv. Kaki (Cajanus cajan) as green manures at three sowing dates and two row spacings at Embrapa-Centro Nacional de Pesquisa de Solos (CNPS), Senador Canedo, GO, Brazil. The experimental design used was a complete randomized block with split-plot and three replicates. Highest yields of dry matter were obtained with C. juncea and C. cajan. The delay in sowing dates to the beginning of the rainy season, reduced yield of fresh and dry matter of all legume species, except black velvet bean. Row-spacings of 0,5 and 0,4 cm did not influence the time for flowering and the yield of fresh and dry matter.